3DoF Model Helicopter with Hybrid Control - Arbab Nighat Khizer; Dai Yaping; Syed Amjad Ali; Xu Xiang Yang (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Dynamics of miniature unmanned helicopter are considered nonlinear and mutually coupled; therefore designing of a stable control becomes a big challenge for researchers. This paper addresses this issue by proposing a hybrid control methodology using both traditional and intelligent control. A 3DoF model helicopter system is used as a controlled platform. This hybrid control used PID as a traditional and fuzzy as an intelligent control so as to take the full advantage of advanced control theory. Proposed hybrid control is evaluated against the fuzzy and PID control through intensive simulation. Results verified that the proposed control has an excellent performance in static as well as dynamic environment as compared to individual PID and fuzzy control. DOI : http://dx.doi.org/10.11591/telkomnika.v12i5.5091